Pozbawienie wolności w celu zbadania stanu psychicznego w prawie polskim - Gardocka, Teresa (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject of these considerations is the deprivation of freedom ordered to diag-nose the state of an individual’s/person’s mental health. Polish law provides for such a diagnostic deprivation of freedom in the event of a suspected offense with a simultaneous doubt as to the person’s sanity at the time of the committing the act (Code of Criminal Procedure), doubt as to mental illness beings a cause of behavior threatening one’s own life or health, or the lives of others (Act on the Protection of Mental Health) and the exist-ence of a mental illness as a reason for incapacitation (Code of Civil Procedure). These legal institutions differ as for constitutional justification (Article 31 point 3) of the Polish Constitution) and their permissible duration. These differences are the main subject of the analysis. Particularly doubtful seems the possibility of diagnostic deprivation of freedom provided for in the proceedings on incapacitation, as to its duration (it may last up to 3 months).
Keywords: pozbawienie wolności; stan psychiczny; zdrowie psychiczne; niezdolność do pracy